Penyuluhan Literasi Keuangan Digital Ekonomi Hijau Terhadap Pemberdayaan UMKM - Randyantini, Vely; Fathihani, Fathihani; Saputri, Ika Puji (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The development and progress of digital technology in the financial services sector can be utilized for business development, especially for MSMEs. However, the lack of digital financial literacy means that MSME players, especially digital-based ones, cannot use digital financial services properly, so many are exposed to illegal online loans. This Community Service activity aims to increase understanding of digital financial literacy as a form of green economic support for MSMEs. Through this activity, it is hoped that it can improve the knowledge of MSME players. Collaboration partners for this activity are 20-30 MSME Business Actors (Aged 20-30 Years), especially those who are already working and have an income who live in the Tanjung Duren area, West Jakarta. The method of implementing community service is carried out by conducting outreach which consists of three stages, namely preparation, implementation and evaluation. The results of the PkM activities show that participants can understand digital financial literacy well, that is, they are able to manage and utilize finances optimally and can use digital financial services according to their business needs